Peran Permainan Tradisional Engklek dalam Mengembangkan Konsep Bilangan di Madrasah Ibtidaiyah - Mudrik Ro’isul Mahbub; Nabila Luthfiana; Fikrotus Sikhah; Dian Mustika Anggraini (IEC: Journal of Educational Innovation, 2026)
This research aims to describe the contribution of the traditional engklek game in developing students' understanding of numbers and counting skills at MI NU Maslakhul Huda. The method used is a descriptive qualitative approach, with data collection through interviews, observation and documentation. Respondents in this study consisted of teachers and class II students at MI NU Maslakhul Huda. Findings from the research revealed that the use of the engklek game in teaching mathematics succeeded in increasing students' enthusiasm, motivation and active participation in calculating activities. The teachers introduced the game by providing an explanation of the rules and linking counting activities to each phase of the game. Students are directed to calculate numbers, solve simple problems, and increase concentration when jumping on one leg. The learning process becomes more interesting, because students can learn while playing, which reduces the fear of making mistakes. Apart from helping students understand the concept of numbers in a real way, the engklek game also trains balance, accuracy and cooperation among students. Thus, the traditional game of engklek can be an effective, interesting, and rooted in local culture mathematics teaching tool to improve students' numeracy skills at the elementary school level.